Andrij Potebnia – a forgotten hero of Polish-Ukrainian relations - Матеуш Каміонка (Cхід, 2022)
Poland and Ukraine have a lot of problems in establishing bilateral remembrance policy, first of all because of the history after World War I, and as well in topic connected to – mostly in frame of stereotypes – the history during The Polish-Lithuanian Commonwealth. Deep russification and anti-Polish state policy, which lasted from XVIII to XXI century, implemented by Russians in Ukraine should be underlined as well. Not only “Ukrainian” meant second category, but also world “Polski Pan” (Polish Lord) had a definite pejorative tone then – it was used even in propaganda during Soviet Invasion in 1920 and 1939. In article will ipso facto be presented one of the forgotten heroes (definitely in Ukraine) which can be a symbol of bilateral international relations. Andrij Potebnia should be one of main actors of building Polish-Ukrainian memory cooperation. The text not only reveals how memory of this officer is presented in Polish Internet today, but also how this forgotten hero of two nations is remembered by local communities in Poland.